Improving user's Web search experience by interactive re-ranking and zooming interfaces - Liu, J.; Chen, H.; Furuse, K.; Ohbo, N. (Journal of Digital Information Management, 2009)
The well-known search engines such as Google, Yahoo! and MSN, are not enough for the advanced users who require user experience, for instance, much more correlative words, or interactive operations applied to returned results such as re-ranking and zooming. To focus on this idea of interactivity, we proposed and implemented interactive interfaces to improve user experience for supporting Web search. they are nice interfaces supporting dynamically changing re-ranking, related word zooming, and related word emphasizing and deemphasizing. It has been served as online search service recently. Our experimental evaluations confirm their convenience and good online performance.
Keywords: Interactive search; Online web search; Re-ranking; Zooming interfaces